The Authority of The Supervisory Board and Legal Protection for Parties Regarding The Loss of The Minutes Of a Deed as Evidence - Agung Iriantoro (Journal Evidence Of Law, 2025)
Notary is a prestigious, noble profession (nobile officium), with high values of nobility and dignity. Thus, in carrying out his duties and position a Notary must be guided normatively by applicable legal regulations and have a responsible attitude towards the authentic deeds he makes. Therefore, the urgency of this research is to analyse the authority of the Supervisory board in providing guidance to Notaries who are negligent in storying their Minutes of deeds and the protection as well as legal certainty of the parties in the event of the loss of Minutes of Deeds, which are evidence for the parties. This research is a normative legal research conducted by examining library materials or secondary data, which commonly referred to library study research. This study concludes that the Minister of law and Human Rights formed the Supervisory board with the aim of supervising and providing guidance to Notaries in carrying out their professional positions as public officials. Supervisory board consists of Regional Notary Supervisory Board, Territory Notary Supervisory Board and Central Notary Supervisory Board. This is made in accordance with its work area, Regional Supervisory Board as the main spearhead has the authority in terms of guidance and examination, one of which is regarding the Minutes of Deeds, which are part of the Notary Protocol. The Regional Supervisiory Board can impose sanctions as a form of guidance on Notaries who commit violations, one of which is negligence in storinfg minutes of deeds. Notary is responsible for the loss of the Minutes of th Deed by making a report to the Indonesian Police as a form of fulfilling the rights and legal certainty regarding the copy of the deed kept by the parties.